2013
DOI: 10.13170/aijst.2.2.704
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Color and Physiological Components of The Postharvest Mango (Mangifera indica L.) Influenced by Different Levels of GA3

Abstract: This experiment consisted of two popular mango varieties in Bangladesh (viz., Langra and Khirshapat) and four different levels of Gibberellic acid (GA3) solution, namely control, 100, 200 and 400 ppm. The two factors experiment was assigned in randomized complete block design with tree replicates. Data obtained from various biochemical analyses in terms of physicochemical properties and shelf life of postharvest mango, were recorded and statistically analyzed for comparison among the mean values using DMRT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
5
2
0
Order By: Relevance
“…The duration of the exposure to 1-MCP and GA3 dipping were 24 hours and 10 minutes, respectively. These results are in accordance with those reported by Islam et al (2013a). They reported that, mango fruits weight loss percentage and decay incidence gradually and significantly increased with prolonging of storage period.…”
Section: Fruit Weight Loss Decay and Marketable Percentagessupporting
confidence: 93%
See 4 more Smart Citations
“…The duration of the exposure to 1-MCP and GA3 dipping were 24 hours and 10 minutes, respectively. These results are in accordance with those reported by Islam et al (2013a). They reported that, mango fruits weight loss percentage and decay incidence gradually and significantly increased with prolonging of storage period.…”
Section: Fruit Weight Loss Decay and Marketable Percentagessupporting
confidence: 93%
“…These results are in harmony with the findings of Chutichudet et al (2016) on mango fruits, who reported that postharvest application of 1-MCP reduced physiological loss in weight in comparison to untreated fruits. Moreover, these results are conformity with the findings of Wahdan et al (2011) and Islam et al (2013a). They reported that, dipping mango fruits in GA 3 reduced weight loss during storage.…”
Section: Fruit Weight Loss Decay and Marketable Percentagessupporting
confidence: 93%
See 3 more Smart Citations